ANALISIS KINERJA UPTD BLK DINAS TENAGA KERJA DAN TRANSMIGRASI KOTA SEMARANG - Adam Setiawan; Maesaroh Maesaroh (Journal of Public Policy and Management Review, 2016)
The level of quality of service depends on the performance of the bureaucracy as public service providers. UPTD BLK Semarang Regional Office of Manpower and Transmigration Department is a public organization which organizes vocational skills training services in the city of Semarang. This research of analysis aims to know the performance of UPTD BLK Semarang city that is focused on the performance of field work skills training as well as know the supported and restricted factor in the achievement of the performance. Performance appraisal as seen from five dimensions i.e. productivity, quality of service orientation, responsiveness, accountability and corporate responsibility, whereas the supported and restricted factor as seen from the human resources and infrastructure. This research used qualitative descriptive approach with an informant employees UPTD BLK Semarang and the user community service. The results of this research show the performance UPTD BLK Semarang Regional Office of Manpower and Transmigration Department not optimal, still found some problems on the dimensions of productivity, quality of service orientation, responsiveness and corporate responsibility, a new dimension of accountability of both categories, in addition to the limited human resources, and infrastructure are less well be factors restricting implementation of performance. Suggestions that can be done to improve performance, i.e. creating coordination and good cooperation with the technical team, improving socialization and sensitivity to the needs of the community and improving the quality of job skills training. As for overcoming the factors restricting the performance with improving the quality and quantity of human resources, adding and revamping infrastructure and determine the target completion results of graduate training.